Adult survival of Arctic terns in the Canadian High Arctic. Issue 1 (1st January 2018) - Mallory, Mark L.; Davis, Shanti E.; Maftei, Mark; Fife, Danielle T.; Robertson, Gregory J.
ABSTRACT: Arctic tern ( Sterna paradisaea ) populations are thought to be in decline across much of their range. For long-lived seabirds, determining adult survival rates is key to understanding current population trends and predicting trajectories. We therefore examined adult survival of terns banded at our field site in the Canadian High Arctic between 2007 and 2016. Apparent adult survival was 0.883, comparable to values for other tern species and for other Arctic larids. However, using this survival rate plus first year survival values from a recent study in Iceland, we project a declining trend for terns in the Canadian High Arctic, consistent with recent reports from local ecological knowledge and limited regional surveys. Our data suggest that low adult survival is not responsible for declining tern populations, and that studies should investigate whether dispersal to new nesting locations may be underway, or that young terns are not surviving well or recruiting to the population.